(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Dengue is the fastest-spreading virus in the world, affecting up to 200,000 people per year and causing 40,000 deaths through the bite of infected mosquitoes. The dengue virus spreads to people when an infected mosquito bites them. About half of the world’s population, or 4 billion individuals, reside in dengue-risk regions. These mosquitoes, which can be found both indoors and outdoors, prefer to bite humans. A person becomes infected after being bitten by a mosquito. Malaria is also spread by these mosquitoes. The results of this analysis in terms of ingredients, procedure, effectiveness, environmental impact, and presentation are Agree. The overall mean obtained by the chemical engineers is 2.92, interpreted as Agree, while the dermatologists obtained an overall mean of 2.96, interpreted as Agree. The T-computed value is 0.706. T-critical is 3.355 with an alpha level of 0.01 and degrees of freedom of 8, indicating there is no significant difference between the two groups of respondents. The respondents recommended including extra vanilla in the ingredients and not boiling the garlic during the procedure. More lemongrass should be added for greater efficacy. Try it with other insects to see how it affects the surroundings. Additionally, the presentation advises that the researchers utilize large bottles.